Large noncollinearity and spin reorientation in the novel Mn2RhSn Heusler magnet - Meshcheriakova, O.; Chadov, Stanislav; Nayak, A. K.; Roessler, U. K.; Kuebler, J.; Andre, G.; Tsirlin, A. A.; Kiss, J.; Hausdorf, S.; Kalache, A.; Schnelle, W.; Nicklas, Michael; et al. (Physical Review Letters, 2014)
Noncollinear magnets provide essential ingredients for the next generation memory technology. It is a new prospect for the Heusler materials, already well known due to the diverse range of other fundamental characteristics. Here, we present a combined experimental and theoretical study of novel noncollinear tetragonal Mn2RhSn Heusler material exhibiting unusually strong canting of its magnetic sublattices. It undergoes a spin-reorientation transition, induced by a temperature change and suppressed by an external magnetic field. Because of the presence of Dzyaloshinskii-Moriya exchange and magnetic anisotropy, Mn2RhSn is suggested to be a promising candidate for realizing the Skyrmion state in the Heusler family. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20